Electron microscopic demonstration of the penetration of liposomes through skin - Schramlová, J; Blazek, K; Bartácková, M; Otová, B; Mardesicová, L; Zizkovský, V; Hulínská, D (Folia biologica, 1997)
To verify the penetration of liposomes through skin, we have used liposomes with encapsulated protein G-gold conjugate in a gel vehicle. Skin samples were examined 2, 4, 24, 48, and 72 h after liposome application. Our findings show that the penetration of liposomes through skin depends mainly on their size. Liposomes up to 600 nm in diameter penetrate through skin rather easily, whereas liposomes 1000 nm and more in diameter remain interiorized in the stratum corneum. The main penetration of liposomes proceeds along the hair sheaths as indicated by larger amounts of free liposomes in the corium of guinea pigs.
Keywords: morčata; keratinocyty; elektronová mikroskopie; Vitamin A; Endocytosis; Humans; Skin; kůže; zlato; lidé; Hair Follicle; králíci; Gold; Time Factors; Microscopy, Electron; Guinea Pigs; vlasový folikul; Animals; endocytóza; zvířata; liposomy; vitamin A; Macrophages; Rabbits; Liposomes; Keratinocytes; časové faktory; makrofágy